Multisystem Inflammatory Syndrome in Children (MIS-C): New challenges of a new era - Dr. Bibhudatta Mishra; Dr. Arjit Mohapatra; Dr. Biswajit Mishra; Dr. Vidya Patwari (Pediatric Review: International Journal of Pediatric Research, 2020)
In the background of a sudden surge of coronavirus disease 2019 (COVID-19) cases, reports of the multisystem inflammatory syndrome in children from different parts of the globe are a matter of concern for physicians. We report a similar case presenting with persisting fever, rashes, bulbar conjunctivitis, abdominal pain, respiratory difficulty, and shock. Initial reports suggestive of high inflammatory markers, neutrophilic leucocytosis, high d-dimer, transaminitis, and found to have COVID 19 IgG antibodies positive in high titer. The echo at the bedside is suggestive of poor LV function with normal coronaries. Managed successfully in PICU with non-invasive ventilation support, ionotropy, aspirin, IVIG, and steroids and discharged. Early referral, a high index of suspicion, prompt recognition of shock, and early management by steroids and intravenous immunoglobulin (IVIG) may bring success.